Cross-Coupling Reactions between Alkenes by C–H Cyclometalation - Lu, Xi; Wang, Yini; Xie, Kailin; Zhang, Jian (Synlett, 2023)
Alkenes are one of the most abundant raw feedstocks and are utilized to construct complex chemicals, whilst cross-coupling reactions using alkenes represents a powerful method toward valuable chemicals. In the past decade, cross-coupling reactions of simple alkenes by chelation-assisted alkenyl C–H functionalization has attracted significant attention due to its atom/step efficiency and excellent Z/E selectivity, proceeding by C–H exo-cyclometalation and endo-cyclometalation. In this account, we summarize transition-metal-catalyzed cross-coupling reactions between alkenes to generate 1,3-dienes via C–H alkenylation,1,4-dienes through C–H allylation, multisubstituted alkenes via hydroalkenylation, and heterocycles by way of tandem alkenyl C–H functionalization/annulation. Asymmetric alkenyl C–H alkenylation to prepare axially chiral aryl 1,3-dienes is also discussed.1 Introduction2 Alkenyl C–H Alkenylation2.1 By endo-Cyclometalation2.2 By exo-Cyclometalation3 Alkenyl C–H Allylation3.1 By endo-Cyclometalation3.2 By exo-Cyclometalation4 Alkenyl C–H Alkylation via Hydroalkenylation5 Cascade Reactions6 Conclusion
Keywords: alkenes; C–H functionalization; cross-coupling; chelation assistance; transition-metal catalysis